FOLATE DEFICIENCY IN OBSTETRICS AND THE PROBLEM OF ITS CORRECTION - V. O. Bitsadze; N. V. Samburova; N. A. Makatsariya; A. L. Mishchenko (IRBIS LLC, 2016)
The article considers the reasons and the role of the folate deficiency in development of the complicated pregnancy and congenital malformations. The biological functions of folate in an organism are described, as well as the role of folate in an exchange of methionine and a hyperhomocysteinemia as one of the reasons of malformations and complications of pregnancy. The role of a genetic mutation of MTHFR as the hyperhomocysteinemia reasons at patients with deficiency of folate and the treatment of the state of the deficiency of folate are discussed.